Resistance is common in paediatric patients failing ART in South Africa. (5th April 2023) - Hunt, Gillian M; Yousif, Mukhlid; Levin, Leon; Ledwaba, Johanna; Steegen, Kim; Kufa, Tendesayi; Zwane, Hloniphile; Kalimashe, Monalisa; Kana, Vibha; Aynalem, Getahun; Perlman, Jaclyn; Ayalew, Kassahun; et al.
Abstract: Background: Minimal data exist on HIV drug resistance patterns and prevalence among paediatric patients failing ART in resource-limited settings. We assessed levels of HIV drug resistance in children with virological failure. Methods: This cross-sectional study, performed from March 2017 to March 2019 in South Africa, enrolled HIV-positive children aged ≤19 years, receiving ART through public health facilities with recent evidence suggestive of virological failure (at least one viral load ≥1000 copies/mL), across 45 randomly selected high-volume clinics from all nine provinces. Resistance genotyping was performed using next-generation sequencing technologies. Descriptive analysis taking into account survey design was used to determine outcomes. Results: Among 899 participants enrolled, the adjusted proportion of HIV drug resistance among children with virological failure was 87.5% (95% CI 83.0%–90.9%). Resistance to NNRTIs was detected in 77.4% (95% CI 72.5%–81.7%) of participants, and resistance to NRTIs in 69.5% (95% CI 62.9%–75.4%) of participants. Overall, resistance to PIs was detected in 7.7% (95% CI 4.4%–13.0%) of children. Conclusions: HIV drug resistance was highly prevalent in paediatric patients failing ART in South Africa, with 9 in 10 patients harbouring resistance to NNRTIs and/or NRTIs. PI-based regimens are predicted to be highly efficacious in achieving virological suppression amongst patients failing NNRTI-based regimens. Scaling up resistance testing amongst patients would facilitate access to second- and third-line regimens in South Africa.